The mobility of companies from OHADA area : research in the light of European and international company law. - (:unkn) unknown (My University, 2017)
Apart from the direct objective of the Organization for the Harmonization of Business Law in Africa (OHADA) to standardize the law, its indirect objective relates to the creation of a large common market. However, regarding the difficulties for companies to transfer their registered office from one member state to another, we can see that the existence of such market is still not a reality for them. Therefore, it appears that the only standardizing of the corporate law by OHADA is not sufficient to allow them to perform their cross-border mergers. This research shows thus that OHADA needs to change and to transform itself to put in place a real right to mobility in the community area for the companies. Like the European Union, it should complete the legal integration by an economic integration setting up a freedom of establishment, including border restructuring operations. But this right to mobility should not be abused. OHADA will have to find a balance between facilitating the mobility and protecting efficiently minority shareholders, employees and third parties rights. Similarly a balance must be struck to solve the conflict of community norms in the restructuring operations legal regime, since it is a recurrent problem for OHADA space.
Keywords: African Research